Georgia Architectural and Historic Properties Survey of Willis St. [5], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Willis St. [5], Sycamore, Turner County, Ga., 1981. Georgian plan house with hipped roof and multiple pedimented gables. Hipped porch is supported by Tuscan columns, and is rounded at the corner. It surrounds the front and left side of the house and is partially filled on the left side, partially screened in front, but mostly open. Gables feature gingerbread bargeboards. Shiplap siding. Double sash windows with 4/4 lights. Transom over front door. Brick piers. Fair condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Willis St. [5], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 54.2 MB (56,881,587 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)